Construção automática de ontologia em Prolog a partir de modelos de processos em BPMN - Gomes, Lina Raylly Moreira (2016)
The Business Process Management Notation (BPMN) enables the modeling of business processes. This modeling is done for some specific purpose, standardize, simulate, document business processes, identify problems, implement solutions among others. However, analysts by carelessness or not well known notation can develop inconsistencies. These, in turn are a problem because difficult to read modeling, lock the process, and can generate syntactic and semantic errors. To solve this problem we propose a solution using logic programming and JAVA; we use logic programming to queries that to answer through inferences and deductions, and JAVA to read and transform the eXtensible Markup Language (XML) from the model to its corresponding code in Prolog. Thus, we developed a Java Desktop in application that uses the API DOM W3C, and receives as input the XML code in a BPMN modeling and returns the code in Prolog regarding this XML code. Finally, we present a query scope that can identify some inconsistencies in process models. With these inconsistencies identified, the improvement process becomes easier and analysts and developers can better understand the process models.